2012
DOI: 10.1007/s00396-012-2588-z
|View full text |Cite
|
Sign up to set email alerts
|

Novel polymer nanocomposite hydrogel with natural clay nanotubes

Abstract: presence of nanoclay in aqueous system. Here, novel natural tube-like nanoparticles, halloysite nanotubes (HNTs), are firstly used as multifunctional cross-linkers for polyacrylamide (PAAm) to form a new type of organic/inorganic hybrid hydrogels. Significant improvements in mechanical properties of the PAAm-HNTs NC gels are found by the addition of HNTs as shown by the static mechanical testing and dynamic viscoelasticity measurement. HNTs are uniformly dispersed in the NC gels from the morphological result. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(55 citation statements)
references
References 37 publications
1
54
0
Order By: Relevance
“…G′ rose sharply while G″ decreased sharply when the frequency increased beyond 100 rad s −1 . When the hydrogels were repeatedly deformed at a high frequency, the polymer chains failed to rearrange themselves within the short time scale of the imposed mechanical deformation, which led to stiffening of the networks . This result further confirmed the formation of hydrogel networks.…”
Section: Resultssupporting
confidence: 53%
“…G′ rose sharply while G″ decreased sharply when the frequency increased beyond 100 rad s −1 . When the hydrogels were repeatedly deformed at a high frequency, the polymer chains failed to rearrange themselves within the short time scale of the imposed mechanical deformation, which led to stiffening of the networks . This result further confirmed the formation of hydrogel networks.…”
Section: Resultssupporting
confidence: 53%
“…As the XRD pattern of the SPI/HNTs/PVA/PTGE film shown, three additional peaks at around 2θ = 12.2°, 19.9° and 25° were observed, corresponding to the crystalline structure of HNTs. This result indicated that HNTs was uniformly dispersed in the SPI matrix and the crystal structure of HNTs was not altered2637.…”
Section: Resultsmentioning
confidence: 91%
“…In the spectrum of MMT, the frequency of the vibrational band at 3616 cm −1 corresponds to the -OH stretching in MMT and the band at 1631 cm −1 corresponds to and H-O-H bending. The peaks at 982 and 843 cm −1 are assigned to Si-O-Si stretching and Al (Mg)-O-H282930.…”
Section: Resultsmentioning
confidence: 99%